I temi liceali di Gramsci: Introduzione - Righi, Maria Luisa (International Gramsci Journal, 2024)
This article is the Italian Introduzione to the three newly discovered essays written by Gramsci while still at the Liceo Dettori in Cagliari. It goes into why they have only recently come to light, and then published in 2022 in the newspaper “Il fatto quotidiano”. The essays turned up in the family papers of the Milanese Communist Party parliamentarian, Francesco Scotti, a Spanish Civil War veteran and then partisan leader (the Maquis and then in Italy). In Milan he had friends associated with Gramscian activities, among them Carlo Gramsci, the younger brother of Antonio. A likely explanation is that Scotti was given these essays by someone in this group to hand them over to the PCI in Rome, probably to Togliatti, but neglected to do this and so they remained forgotten for years. The essays themselves can with certainty be dated to Gramsci’s last year at the high school since the signature of the professore is Vittorio Amedeo Arullani, who had replaced Raffa Garzia as Gramsci’s Italian teacher. The essay subjects assigned were quotations from the sixteenth century writer Giovanni Della Casa’s treatise, Il Galateo, and the two poets, Leopardi and Carducci. For all of these essays Arullani gave positive judgments and very high grades. One sees a student very open to the currents of thought of the period, whose essays prefigure themes that later come explicitly to the fore in his journalistic work and even in the Prison Notebooks (artistic currents and aesthetics, Americanism, the “mummification” of culture, the figure of Stenterello, Kant’s “beheading” of God, Jesuitism and so on).